In Situ Crystalline AlN Passivation for Reduced RF Dispersion in Strained‐Channel AlN/GaN/AlN High‐Electron‐Mobility Transistors. Issue 4 (14th October 2021) - Chaudhuri, Reet; Hickman, Austin; Singhal, Jashan; Casamento, Joseph; Xing, Huili Grace; Jena, Debdeep
Abstract : The recent demonstration of ≈ 2 W mm −1 output power at 94 GHz in AlN/GaN/AlN high‐electron‐mobility transistors (HEMTs) has established AlN as a promising platform for millimeter‐wave electronics. The current state‐of‐art AlN HEMTs using ex situ‐deposited silicon nitride (SiN) passivation layers suffer from soft gain compression due to trapping of carriers by surface states. Reducing surface state dispersion in these devices is thus desired to access higher output powers. Herein, a potential solution using a novel in situ crystalline AlN passivation layer is provided. A thick, 30+ nm‐top AlN passivation layer moves the as‐grown surface away from the 2D electron gas (2DEG) channel and reduces its effect on the device. Through a series of metal‐polar AlN/GaN/AlN heterostructure growths, it is found that pseudomorphically strained ≤ 15 nm thin GaN channels are crucial to be able to grow thick AlN barriers without cracking. The fabricated recessed‐gate HEMTs on an optimized heterostructure with 50 nm AlN barrier layer and 15 nm GaN channel layer show reduction in dispersion down to 2 − 6 % compared with 20 % in current state‐of‐art ex situ SiN‐passivated HEMTs. These results demonstrate the efficacy of this unique in situ crystalline AlN passivation technique and should unlock higher mm‐wave powers in next‐generation AlN HEMTs. Abstract : Herein, a novel in situ passivation technique for III‐nitride high‐electron‐mobility transistors (HEMTs) is demonstrated using a crystalline AlN layer to move the surface states away from the 2D electron gas (2DEG) channel. In situ‐passivated AlN/GaN/AlN HEMTs show drastic reduction in DC‐RF dispersion of ≈2%–6%, compared with ≈20% in current state‐of‐art ex situ silicon nitride (SiN)‐passivated AlN HEMTs.